Control of dTTP pool size by anaphase promoting complex/cyclosome is essential for the maintenance of genetic stability - Ke, Po-Yuan (Cold Spring Harbor Laboratory Press, 2005)
Anaphase promoting complex/cyclosome (APC/C)-mediated proteolysis is essential for chromosome segregation, mitotic exit, and G1 entry. Here, we show the importance of APC/C in the control of dTTP pool size in mammalian cells. Two enzymes, thymidine kinase 1 (TK1) and thymidylate kinase (TMPK), involved in dTTP formation are the targets of the APC/C pathway. We demonstrate that TMPK is recognized and degraded by APC/C–Cdc20/Cdh1-mediated pathways from mitosis to the early G1 phase, whereas TK1 is targeted for degradation by APC/C–Cdh1 after mitotic exit. Overexpression of wild-type TK1 and TMPK induces a four- to fivefold increase in the cellular dTTP pool without promoting spontaneous mutations in the hprt (hypoxanthine-guanine phosphoribosyl transferase) gene. In contrast, coexpression of nondegradable TK1 and TMPK expands the dTTP pool size 10-fold accompanied by a drastic dNTP pool imbalance. Most interestingly, disruption of APC/C proteolysis of TK1 and TMPK leads to growth retardation and a striking increase in gene mutation rate. We conclude that down-regulation of dTTP pool size by the APC/C pathway during mitosis and the G1 phase is an essential means to maintain a balanced dNTP pool and to avoid genetic instability.